Global burden of childhood developmental intellectual disability caused by iodine deficiency from 1990 to 2021 and projection to 2040 - Liu, Zihao; Lin, Youhui; Liang, Li; Li, Xuanyi; Wang, Zhiyin; Cheng, Wei (Frontiers in Public Health, 2025)
BackgroundIodine deficiency remains a leading preventable cause of childhood developmental intellectual disability (DID), imposing a substantial and enduring global public health burden; despite decades of global efforts to combat iodine deficiency, persistent health inequalities and uneven progress highlight critical gaps. This study aimed to comprehensively analyze the global burden, temporal trends, and inequalities in childhood DID attributable to iodine deficiency from 1990 to 2021 and projected to 2040. Our results will inform evidence-based public health policies, especially in the most affected areas.MethodsThis observational study utilized secondary data from the Global Burden of Disease 2021 study, which covered 204 countries and territories. The burden of DID was stratified by age, sex, and region. Age-standardized prevalence rates (ASPR) and age-standardized years lived with disability (ASYR) were calculated. Trends were analyzed using joinpoint regression by estimated the annual percent change and average annual percent change (AAPC). Health inequalities were assessed using the slope index of inequality. Forecasts to 2040 were generated using the Bayesian age-period-cohort model.ResultsGlobal ASPR declined from 43.06 to 8.96/100,000 (AAPC = −4.95) and ASYR from 7.71 to 1.67/100,000 (AAPC = −4.81) between 1990 and 2021. Despite this progress, low socio-demographic index (SDI) regions, particularly Central Sub-Saharan Africa and South Asia, continue to bear the highest burden. Somalia had the highest 2021 rates (ASPR: 47.86; ASYR: 9.40/100,000). SDI correlated negatively with ASPR (R = −0.62, p < 0.001) and ASYR (R = −0.62, p < 0.001). The slope index showed reductions in decline rates for prevalence (−19.256 [95%CI: −26.992, −11.520] to −12.531 [−16.107, − 8.955]) and YLDs (−3.662 [−5.047, − 2.276] to −2.451 [−3.144, − 1.757]), though overlapping confidence intervals indicated non-significance. Projections suggest stable ASPR/ASYR by 2040 but rising absolute cases (489,983 prevalent cases; 85,491 YLDs).ConclusionWhile public health interventions have reduced the global burden of DID caused by iodine deficiency, persistent inequalities in vulnerable regions demand urgent policy action: scaling up universal salt iodization programs in high-burden areas, integrating maternal nutrition education into primary healthcare systems, and prioritizing resource allocation to regions with stagnating SDI indices.